DAMPAK PROGRAM PEMBAHARUAN AGRARIA NASIONAL (PPAN) TERHADAP KEADAAN SOSIAL EKONOMI DAN EKOLOGI MASYARAKAT LOKAL - Maharani Kusuma Ningtyas, Pitaloka; Hadi Dharmawan, Arya (Sodality: Jurnal Sosiologi Pedesaan, 2010)
The objectives of this research are: (1) to compare the social-economic condition of communities before and after the National Agrarian Reform Program (PPAN); (2) to know the alteration of land placement (3) to explore the differences of perception from local communities about PPAN. This research was using qualitative and quantitative method. The qualitative method was supported by in-depth interview for collecting data. In the other hand, quessionaire used to be a research instrument to support quantitative method. There were 60 respondents who got PPAN program in this research which selected by purposive sampling technique.